Synthesis of carbazole dendrimers as host materials for organic light emitting diodes / Zainal Abidin Hasan - Zainal Abidin, Hasan (2017)
Four new types of carbazole dendrimers were successfully synthesized namely 1, 4-bis (3, 6-bis (3, 6-ditert-pentyl-carbazol-9-yl)carbazol-9-yl)benzene (13), 1, 3-bis (3, 6-bis (3, 6-ditert-pentyl-carbazol-9-yl)carbazol-9-yl)benzene (14), 4, 4'-bis (3, 6-bis (3, 6-ditert-pentyl-carbazol-9-yl)carbazol-9-yl)biphenyl (15), and 4, 4'-bis (3, 6-bis (3, 6-ditert-pentyl-carbazol-9-yl)carbazol-9-yl)-2,2'-dimethylbiphenyl (16) in six steps. Synthetic route involves Ullmann reaction process as a key reaction to obtain the final products. The dendrimers were isolated in moderate yield between 40-65 % after purification by column chromatography and recrystallization. These dendrimers were fully characterized by NMR, MALDI-TOF mass spectroscopy and CHN analysis. The pure dendrimers were further studied for their optical properties by UV-Vis, fluorescence and low-temperature phosphorescence. The thermal properties of the dendrimers have been study by TGA and DSC analysis. Their electrochemical properties were measured by cyclic voltammetry (CV) to determine their HOMO and LUMO energy levels. All of the dendrimers showed good thermal stability, high triplet energy and appropriate HOMO and LUMO energy levels to serve as host materials for OLEDs. Compound 16 was found to be the best choice to be used as host material for blue, green and red OLEDs because of its high triplet energy (ET = 2.82 eV) along with high glass transition temperature (Tg = 270 °C), high thermal decomposition stability (Td = 470 °C) and suitable HOMO level (EHOMO = -5.24 eV). Compound 16 was used as a host material in the fabrication of single-layer, double-layer and multi-layer devices for blue, green and red OLEDs by a solution-process method. An increment in device efficiency was observed from single layer to double layer devices and further increment can be observed for multilayer devices. The morphology of the thin films was analysed by atomic force microscopy (AFM), which revealed that fluorinated alcohol can form a good thin film with low surface roughness compared to normal alcohol. Fluorinated alcohol has been used to increase the electron injection property of the devices and enable fabrication of electron transport layer through wet process.